Low-NOX combustion of biogas from palm oil mill effluent using flameless combustion - Hamzah, Afiqah (2015)
An experimental study of flamelesscombustion in a laboratory-scale furnace using naturalgas, simulated biogas and palm-oil-mill-effluent(POME) derived biogas. Flameless combustion regimeis achieved fornatural gas, simulated biogas and POMEbiogas. POME biogas flameless combustion has slightlylower average furnace temperature (2.69% reduction)due to increased inert gas in the furnace chamber.Flameless combustion produce larger and more uniformcombustion area (Rtu= 0.097) compared to conventionalflame combustion(Rtu=0.21). NOXemissionmeasurement has shown reduced NOXemission inflameless combustionof natural gas, POME biogas andsimulated biogas with average of 6 ppm.